Cultural pasts essays in early Indian history - Thapar, Romila (New Delhi Oxford Universitry Press, 1999)
Cultural pasts is a collection of papers pertaining to early Indian history, written over the last thirty years and published in varous journals.The focus is on the changing dimensions of social and cultural history. The essays have been grouped into nine
Keywords: India-History-19th century; History,Ancient